2002
DOI: 10.1124/jpet.102.044370
|View full text |Cite
|
Sign up to set email alerts
|

5-Hydroxytryptamine 1A Receptor Activation Protects againstN-Methyl-d-aspartate-Induced Apoptotic Cell Death in Striatal and Mesencephalic Cultures

Abstract: Apoptosis and glutamate-mediated excitotoxicity may play a role in the pathogenesis of many neurodegenerative disorders, including Parkinson's disease (PD). In the present study, we investigated whether stimulation of the 5-hydroxytryptamine 1A (5-HT1A) receptor attenuates N-methyl-D-aspartate-(NMDA) and 1-methyl-4-phenylpyridinium (MPP ϩ )-induced apoptotic cell death in cell culture models. A brief exposure (20 min) of M213-2O striatal cells to NMDA and glutamate produced a delayed increase in caspase-3 acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 42 publications
4
33
0
Order By: Relevance
“…However, the underlying mechanisms remain unclear. Studies have shown that glutamate activates caspase 3 in cultured cortical neurons, striatal neurons, and mesencephalic neurons (Liu and Zhu, 1999;Madhavan et al, 2003). Our previous study also demonstrates that glutamate ubiquitously elicits the activation of caspases 2, 3, 6, 8, and 9 (Chi et al, 2005).…”
Section: Discussionmentioning
confidence: 92%
“…However, the underlying mechanisms remain unclear. Studies have shown that glutamate activates caspase 3 in cultured cortical neurons, striatal neurons, and mesencephalic neurons (Liu and Zhu, 1999;Madhavan et al, 2003). Our previous study also demonstrates that glutamate ubiquitously elicits the activation of caspases 2, 3, 6, 8, and 9 (Chi et al, 2005).…”
Section: Discussionmentioning
confidence: 92%
“…5-HT1A receptor stimulation rescued cultured hippocampal neurons from glutamate-mediated excitotoxicity and protected against ischemic neuronal cell death (Nakata et al, 1997;Harkany et al, 2001;Madhavan et al, 2003). Previous studies have shown that 5-HT1A receptor stimulation can (Strosznajder et al, 1996;Matsuyama et al, 1997;Madhavan et al, 2003). Other mechanisms, in addition to inhibition of N-methyl-D-aspartate (NMDA)-induced Ca 2+ influx, may be important in the neuroprotection resulting from 5-HT1A receptor stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Other mechanisms, in addition to inhibition of N-methyl-D-aspartate (NMDA)-induced Ca 2+ influx, may be important in the neuroprotection resulting from 5-HT1A receptor stimulation. Madhavan et al suggested that 5-HT1A receptor stimulation protects against NMDA-mediated apoptotic cell death in both striatal and nigral neurons (Madhavan et al, 2003). Prehn et al (1993) suggest that 5-HT, released during ischemia, may have protective effects in the pathophysiology of ischemic brain damage through a direct action on neurons mediated via the inhibitory 5-HT1A receptor subtype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apoptotic cells in vitro were detected in a standard nuclear stain with the Hoechst dye 33342 and cells with apoptotic (condensed and/or fragmented) nuclei were quantified as described (Madhavan et al, 2003). Pure growth factor proteins provided in the kit were used to establish standard curves for quantification.…”
Section: Detection Of Apoptosismentioning
confidence: 99%